Analisis Konten Kesehatan Mental Dalam Karya Musik Kendrick Lamar - Muhammad Fandy Erlambang; Ikhsan Fuady; S. Kunto Adi Wibowo (Universitas Negeri Surabaya, 2021)
During the 2000s and 2010s, mental health problems of Generation Z youth increased, but efforts to seek help decreased. However, rap music can be one of the several interventions that can help them. In this content analysis research, the authors apply a quantitative analysis method to the lyrics contained in the music of Kendrick Lamar, one of the most popular rap musicians during the 2010s. The analysis was conducted on a sample of 58 Kendrick Lamar songs to find the number of mental health references in his musical works from 2011 to 2017. The sampling technique used was purposive sampling. Data analysis techniques include frequency analysis, Cochran-Armitage test for trends in linear proportions, and cross-tabulations test using SPSS. Based on analysis results, it was found that 31 of the 58 songs in the sample contained mental health references. Mental health references in Kendrick Lamar's music increased from 2011 to 2012, but decreased from 2012 to 2017. The mental health references found were also related to contributing factors such as environmental conditions, spiritual beliefs, and love life. The writing of this research is expected to contribute to the realm of content analysis of rap music and popular music as a whole.